Fetal plane classification from 2D-ultrasound images leveraging squeeze and excitation self-attention mechanism for feature recalibration in MedMamba - Riju, Tanjim Islam; Ramisha, Tahsin Tanim; Aksa, Nusrat Billah; Kabir, Johan H (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.